Proline Accumulation in Developing Grapevine Fruit Occurs Independently of Changes in the Levels of Δ(1)-Pyrroline-5-Carboxylate Synthetase mRNA or Protein - Stines, Anna P. (American Society of Plant Physiologists, 1999)
Mature fruit of grapevine (Vitis vinifera) contains unusually high levels of free proline (Pro; up to 24 μmol or 2.8 mg/g fresh weight). Pro accumulation does not occur uniformly throughout berry development but only during the last 4 to 6 weeks of ripening when both berry growth and net protein accumulation have ceased. In contrast, the steady-state levels of both the mRNA encoding V. vinifera Δ(1)-pyrroline-5-carboxylate synthetase (VVP5CS), a key regulatory enzyme in Pro biosynthesis, and its protein product remain relatively uniform throughout fruit development. In addition, the steady-state protein levels of Pro dehydrogenase, the first enzyme in Pro degradation, increased throughout early fruit development but thereafter remained relatively constant. The developmental accumulation of free Pro late in grape berry ripening is thus clearly distinct from the osmotic stress-induced accumulation of Pro in plants. It is not associated with either sustained increases in steady-state levels of P5CS mRNA or protein or a decrease in steady-state levels of Pro dehydrogenase protein, suggesting that other physiological factors are important for its regulation.